Model home eaudiobook A novel. - Solomon, Rivers (Macmillan Audio, 2024)
Welcome to Rivers Solomon's dark and wondrous Model Home , a new kind of haunted-house novel. The three Maxwell siblings keep their distance from the lily-white gated enclave outside Dallas where they grew up. When their family moved there, they were the only Black family in the neighborhood. The neighbors acted nice enough, but right away bad things, scary things—the strange and the unexplainable—began to happen in their house. Maybe it was some cosmic trial, a demonic rite of passage into the upper-middle class. Whatever it was, the Maxwells, steered by their formidable mother, stayed put, unwilling to abandon their home, terrors and trauma be damned. As adults, the siblings could finally get away from the horrors of home, leaving their parents all alone in the house. But when news of their parents' death arrives, Ezri is forced to return to Texas with their sisters, Eve and Emanuelle, to reckon with their family's past and present, and to find out what happened while they were away. It was not a "natural" death for their parents . . . but was it supernatural? Rivers Solomon turns the haunted-house story on its head, unearthing the dark legacies of segregation and racism in the suburban American South. Unbridled, raw, and daring, Model Home is the story of secret histories uncovered, and of a queer family battling for their right to live, grieve, and heal amid the terrors of contemporary American life. A Macmillan Audio production from Farrar, Straus and Giroux.